Cultural Fusion in Pesantren: Navigating Islamic Customs and Javanese Traditions in Kediri, Suburban Indonesia - Waluyo, Bagus; Huda, M. Dimyati (RaSAIL Media Group, Semarang, Indonesia, 2025)
This study examines how Javanese customs integrate with Islamic practices in pesantren (Islamic boarding schools) in suburban Kediri, Indonesia, and identifies key influencing factors. We used a phenomenological approach to analyze six pesantren students' experiences (gender-balanced, aged 17-23) through in-depth interviews. Findings reveal two main insights: First, cultural fusion manifests through practices like wearing a sarong during prayers, using local dialects in recitations, and incorporating slametan (communal feasts) into Islamic events, demonstrating Islam's cultural adaptability. Second, this integration is facilitated by inclusive leadership (religious scholars reconciling traditions with Islamic principles) and intergenerational dialogue (elders mentoring youth about ancestral customs). However, tensions emerge from generational divides and community disagreements over certain practices. The study highlights musyawarah (consensus-building discussions) as crucial for conflict resolution. These findings advance the understanding of cultural-Islamic hybridity in educational institutions, suggesting that Islamic education policies should formally incorporate local wisdom. Future research could compare urban/rural contexts or examine digital media's role in cultural transmission.